The future of precision medicine in personalized cancer treatment - Bhoyar, Naina; Nirmal Chandu, Himanshu (Journal of Neonatal Surgery, 2025)
The field of cancer treatment has witnessed significant advancements with the emergence of precision medicine, which tailors treatment based on individual genetic, environmental, and lifestyle factors. This research explores the future of precision medicine in the context of personalized cancer treatment, focusing on the application of advanced technologies such as genomic sequencing, biomarker discovery, and targeted therapies. The integration of artificial intelligence (AI) and machine learning (ML) in precision oncology is revolutionizing the way we diagnose, predict, and treat cancer. By identifying specific genetic mutations and molecular characteristics unique to each patient, personalized cancer treatments can improve efficacy, reduce side effects, and increase survival rates. This paper delves into the challenges and potential of precision medicine in oncology, highlighting future directions and the role of interdisciplinary collaboration in advancing personalized cancer treatment.